Different Simultaneous Sleep States in the Hippocampus and Neocortex - Emrick, Joshua J. (Sleep, 2016)
STUDY OBJECTIVES: Investigators assign sleep-waking states using brain activity collected from a single site, with the assumption that states occur at the same time throughout the brain. We sought to determine if sleep-waking states differ between two separate structures: the hippocampus and neocortex. METHODS: We measured electrical signals (electroencephalograms and electromyograms) during sleep from the hippocampus and neocortex of five freely behaving adult male rats. We assigned sleep-waking states in 10-sec epochs based on standard scoring criteria across a 4-h recording, then analyzed and compared states and signals from simultaneous epochs between sites. RESULTS: We found that the total amount of each state, assigned independently using the hippocampal and neocortical signals, was similar between the hippocampus and neocortex. However, states at simultaneous epochs were different as often as they were the same (P = 0.82). Furthermore, we found that the progression of states often flowed through asynchronous state-pairs led by the hippocampus. For example, the hippocampus progressed from transition-to-rapid eye movement sleep to rapid eye movement sleep before the neocortex more often than in synchrony with the neocortex (38.7 ± 16.2% versus 15.8 ± 5.6% mean ± standard error of the mean). CONCLUSIONS: We demonstrate that hippocampal and neocortical sleep-waking states often differ in the same epoch. Consequently, electrode location affects estimates of sleep architecture, state transition timing, and perhaps even percentage of time in sleep states. Therefore, under normal conditions, models assuming brain state homogeneity should not be applied to the sleeping or waking brain. CITATION: Emrick JJ, Gross BA, Riley BT, Poe GR. Different simultaneous sleep states in the hippocampus and neocortex. SLEEP 2016;39(12):2201–2209.